2018
DOI: 10.1186/s12888-018-1932-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct and moderating effects of personality on stigma towards mental illness

Abstract: BackgroundWhile many studies have explored the concept and correlates of stigma towards individuals with mental illness, few have investigated the role of personality in this process. In the current study, we firstly examined the relationship between personality and stigma towards mental illness; and then explored the moderating effects of personality traits on the relationship between contact experience/s and stigma.MethodsParticipants were recruited from public medical (N = 502) and nursing schools (N = 500)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 44 publications
8
44
1
1
Order By: Relevance
“…First, by pointing at the importance of individual differences on the development of negative attitudes toward patients, they suggest that it may be necessary to consider these differences when addressing the problem of stigma among mental health professionals, especially in the earlier stages of education. Our results are in line with previous studies exploring samples of college students [36] and healthcare students [37], showing a negative association between stigma and two dimensions of personality, namely agreeableness and openness. Those features may be accompanied by better empathic and communication skills [73], which in turn may affect the type of contact with the patient.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, by pointing at the importance of individual differences on the development of negative attitudes toward patients, they suggest that it may be necessary to consider these differences when addressing the problem of stigma among mental health professionals, especially in the earlier stages of education. Our results are in line with previous studies exploring samples of college students [36] and healthcare students [37], showing a negative association between stigma and two dimensions of personality, namely agreeableness and openness. Those features may be accompanied by better empathic and communication skills [73], which in turn may affect the type of contact with the patient.…”
Section: Discussionsupporting
confidence: 93%
“…Mental health service organizations should consider implementation of personality and burnout assessments to promptly intervene and minimize stigma among mental health professionals. Further, as suggested by Yuan et al [37], since personality traits continue to develop, especially during young adulthood, future studies should address the role of personality when testing antistigma interventions, especially when they are directed to early stages of education of future healthcare professionals. Finally, given the importance of recovery orientation for stigma research [81][82][83], future studies should address the issue of the relationship among personality traits, stigmatizing beliefs, and recovery orientation among mental health professionals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The participants were asked how they normally feel regarding several positive feelings and emotions, such as interest, excitement, and enthusiasm (''positive affect''). Those in the schizophrenia highest stigma subgroup presented significantly lower scores in this dimension, which was similar to the findings of Yuan et al, 35 who found a negative association between openness to experience and all three stigma domains. However, when comparing the five personality characteristics, including openness, we found no differences among the three subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…The Depression Stigma Scale has been defined as a good instrument to measure attitudes towards depression (Fusar-Poli et al, 2020) and has been used in recent studies in a wide range of cultures (Hanlon & Swords, 2020; Singh et al, 2019; Yang et al, 2020; Yuan et al, 2018) therefore, the detailed study of its psychometric properties is of an enormous value to the understanding and research of depression stigma, as well as the study of the effects of anti-stigma campaigns and the development of effective stigma-reduction interventions.…”
Section: Introductionmentioning
confidence: 99%